The Impact of COVID-19 on the Canadian Economy - Islam, Sadequl; Tarannum, Tahsina (Archives of Business Research, 2020)
This paper examines various types of effects of COVID-19 on Canadian businesses and industrial sectors. Using the data from Labour Force Surveys, the paper explores the impact of COVID-19 on the Canadian labour market. The paper also investigates the relationship between the intensity of lockdown measures ( stringency index) and the unemployment rate for Canada and selected countries. The main findings are the following: 1)The businesses which faced a high level of decreases in demand are food &accommodation, arts, entertainment, and recreation and retail trade; 2) Small businesses witnessed a higher level of decrease in demand compared to large businesses; 3) The goods- producing industries, especially motor vehicle and parts producing industries experienced the steepest decline in growth rates; 4)The pandemic adversely affected the jobs of women, workers with high school education, and young workers; 5) Finally, it appears that there is a weak positive relationship between the Stringency Index and the unemployment rate across selected countries including Canada.